2016
DOI: 10.1039/c6cc05881g
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the composition and formation of solid products in lithium–sulfur batteries by using an experimental phase diagram

Abstract: The lithium-sulfur rechargeable battery has been studied intensively as a candidate for the high specific energy market, which has applications in electric vehicles, portable devices and grid energy storage. [1][2][3][4][5] The theoretical specific energy is ca., which is notably higher than the lithium-ion battery. Several other advantages of using sulfur as the positive electrode include its abundance, low cost and nontoxicity. The theoretical specific capacity of sulfur (1672 A h kg The reduction of S 8 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 22 publications
3
30
0
Order By: Relevance
“…Following Chen et al . and Dibden et al . a solubility for long‐chain polysulfides of the order of 1 M in S is expected, which would imply that precipitation of discharge products should take place before the peak, although there is no obvious difference in the voltage profiles between the cells (Supporting Information, Figure S4).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Following Chen et al . and Dibden et al . a solubility for long‐chain polysulfides of the order of 1 M in S is expected, which would imply that precipitation of discharge products should take place before the peak, although there is no obvious difference in the voltage profiles between the cells (Supporting Information, Figure S4).…”
Section: Resultsmentioning
confidence: 87%
“…At an E/S ratio of 6 μ L mgS-1 , the dissolution of all sulfur in the electrode to form the polysulfide Li2 S6 without any precipitation of Li2 S implies an increase in the lithium ion concentration from 1.25 M to close to 3 M. A decrease in the ionic conductivity of the order of a factor of two is a reasonable expectation as a result of this concentration change . Assuming all elemental sulfur is able to dissolve out of the positive electrode — that is, it is not rendered inactive by a lack of electrolyte access — an E/S ratio of 6 μ L mgS-1 is equal to 167 gS L −1 , or a concentration of 5.2 M in S. This concentration is lower than at the congruent point in the phase diagram as determined for lithium polysulfides in DOL by Dibden et al ., so it is reasonable to assume that all sulfur exists in solution at this point. It has also been suggested that the increase may be related to charge transfer at the negative electrode .…”
Section: Resultsmentioning
confidence: 99%
“…The maximum dissolved concentration of stoichiometric Li 2 S 8 in 2 M LiTFSI in HME/DOL (9:1) is 50 mM as determined by UV/VIS measurements (Figure S1, Supporting Information). Thus, the concentration of dissolved atomic sulfur [S] equals 0.4 m in 2 m LiTFSI in HME/DOL (9:1), which is considerably lower than in DOL/DME electrolytes ([S] ≈ 6 m ) …”
Section: Resultsmentioning
confidence: 99%
“…As a matter of fact, the energy density of practical Li-S batteries strongly depends on the E/S ratio. [2][3][4] The E/S ratio sets an upper bound on LiPS dissolution, and the maximum solubility of LiPS species reported in the widely used ether solution ([S] = ∼6 M) 5 corresponds to an E/S ratio of 5.2 mL g −1 . If the minimum E/S ratio is determined by LiPS solubility, then in the above case electrolyte weight will dominate the battery weight and the theoretical specific energy of an ideal Li-S cell is less than 500 Wh kg −1 (see Supplementary Material).…”
mentioning
confidence: 99%